Role of oncomarkers in diagnosis of multiple primary neoplasms of female reproductive tract - Yu. G. Payanidi; V. M. Shelepova; N. V. Chkhikvadze; A. Yu. Kashurnikov; D. S. Ogay; V. Yu. Selchuk (Опухоли женской репродуктивной системы)
Complex measurements of tumor markers help to improve the diagnosis of multiple primary neoplasms (MPN) significantly. For breast- ovarian MPN CA-125 was increased in 92.6 % and CA-153 — in 81.6 %. In patients with ovarian-colorectal MPN CA-125 was increased in 79.0 % and carcinoembryonic antigen — in 90.0 %.